Przemiany tożsamości mieszkańców Ziem Zachodnich i Północnych = Identity transformations of the inhabitants of Western and Northern lands - Sakson, Andrzej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article discusses the contribution of organisations to the creation of the new social order after 1989, especially in the ?eld of treasuring the past and forming a new democratic reality on the local and regional scale. Examples include activities of the "Borussia" Cultural Community in Olsztyn and the "Mazurska" Community in Giżycko. These societies propagate the idea of open regionalism as well as open localness following the motto "Act locally, think globally".
Keywords: otwarty regionalizm; region; współpraca regionalna; Ziemie Zachodnie i Północne